Utilização de lâmpadas de LED em distintas intensidades luminosas e seus efeitos no desempenho e comportamento de frangos de corte - Dias, Elisandro Rafael (2015)
Brazil is emerging in the world poultry market due to high quality of these products and the wide variety of cuts and industrialized, showing up dynamic, competitive and willing to adapt the industrial processes to the requirements of this segment. Various practices related to the management of broilers have been implemented aimed at improving production rates. Therefore, the greater the care at all stages of creation, the better the results achieved in the performance parameters and the final quality of the product, beyond the customer service market. Environmental control is fundamental premises, especially in relation to the lighting system that directly influences the performance and behavior of birds. The lighting system in controlled environments has been revised, incandescent bulbs normally used were replaced by fluorescent lamps with new technologies that are being proposed, such as LED lamps (Light Emitting Diode). LED bulbs are more energy efficiency and durability, as the light emitted is cold, not dissipating energy as heat. In addition to allowing the use in the preference wave length for broilers. Therefore, this study evaluated the effects of different colors of LED lamps and intensities on the performance and behavior of broilers.